Nickel‐Catalyzed Direct Carboxylation of Olefins with CO2: One‐Pot Synthesis of α, β‐Unsaturated Carboxylic Acid Salts. Issue 51 (30th October 2014) - Huguet, Núria; Jevtovikj, Ivana; Gordillo, Alvaro; Lejkowski, Michael L.; Lindner, Ronald; Bru, Miriam; Khalimon, Andrey Y.; Rominger, Frank; Schunk, Stephan A.; Hofmann, Peter; Limbach, Michael
Abstract The nickel‐catalyzed direct carboxylation of alkenes with the cheap and abundantly available C1 building block carbon dioxide (CO2) in the presence of a base has been achieved. The one‐pot reaction allows for the direct and selective synthesis of a wide range of α, β‐unsaturated carboxylates (TON>100, TOF up to 6 h−1, TON=turnover number, TOF=turnover frequency). Thus, it is possible, in one step, to synthesize sodium acrylate from ethylene, CO2, and a sodium salt. Acrylates are industrially important products, the synthesis of which has hitherto required multiple steps.